2020
DOI: 10.3389/feduc.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into First Grade Students' Development of Conceptual Numerical Understanding as Drawn From Progression-Based Assessments

Abstract: Early numeracy has been found to be one of the strongest predictors for later success in learning. Equipping children with a sound conceptual numerical understanding should therefore be a focus of early primary school mathematics. Assessments that are aligned to empirically validated learning progressions can support teachers to understand their students learning better and target instruction accordingly. This study examines numeracy learning of 101 first grade students over the course of one school year using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…With regard to previous research on LPM instruments in the field of computation, Christ et al (2008) conclude that the use of more systematic sampling and item construction would improve the quality of LPM. To date, there has been little literature on the investigation on DGICs in the field of basic mathematical skills and for developing LPM (e.g., Balt et al, 2020;Ehlert et al, 2013). However, for the theory-based construction of test items for LPM, it is necessary to obtain valid information about which characteristics influence the difficulty of an item.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to previous research on LPM instruments in the field of computation, Christ et al (2008) conclude that the use of more systematic sampling and item construction would improve the quality of LPM. To date, there has been little literature on the investigation on DGICs in the field of basic mathematical skills and for developing LPM (e.g., Balt et al, 2020;Ehlert et al, 2013). However, for the theory-based construction of test items for LPM, it is necessary to obtain valid information about which characteristics influence the difficulty of an item.…”
Section: Discussionmentioning
confidence: 99%
“…14, No. 1 (2022) little literature available on the investigation of difficulty-generating item characteristics (DGICs) in the area of basic mathematical competencies that can be used for systematic LPM item construction (e.g., Balt et al, 2020). The present study addresses this research gap by focusing on the design and evaluation of an item generation system, applying theory-based modeling of item complexity using LLTM to analyze items exemplarily for an LPM addition and subtraction test for numbers up to 100.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of early numeracy experience as the foundation for mathematical learning in school is frequently reported. To demonstrate, the past studies found a significant predictive link between the verbal counting skills (Koponen, Aunola & Nurmi, 2019), subitising (Hannula-Sormunen, Lehtinen & Räsänen, 2015, basic arithmetics (Singer & Strasser, 2017;Pardo, et al, 2020), and number concepts (Balt, Fritz & Ehlert, 2020) in early years with later mathematics performance in school. Sobkow, Olszewska and Traczyk (2020) and Darriet, et al (2020) claimed that the numerical competency could further predict preferences in real-life choices.…”
Section: Children's Ability In Numeracymentioning
confidence: 97%
“…If children solved at least 75% of the items of a level, they were assigned to the corresponding level. The highest achieved level was recorded as the current conceptual level of place value understanding (for similar approaches see Lee and Sarnecka, 2009;Ricken et al, 2013;Fritz et al, 2017;Balt et al, 2020). To address lucky guesses and mistakes, children did not have to solve all items of a level to be considered having developed the concept of the level.…”
Section: Place Value Understandingmentioning
confidence: 99%